2018
DOI: 10.1038/s41594-017-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of TRPV5 channel inhibition by econazole revealed by cryo-EM

Abstract: The transient receptor potential vanilloid 5 (TRPV5) channel is a member of the transient receptor potential (TRP) channel family, which is highly selective for Ca2+, that is present primarily at the apical membrane of distal tubule epithelial cells in the kidney and plays a key role in Ca2+ reabsorption. Here we present the structure of the full-length rabbit TRPV5 channel as determined using cryo-EM in complex with its inhibitor econazole. This structure reveals that econazole resides in a hydrophobic pocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
147
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(157 citation statements)
references
References 60 publications
10
147
0
Order By: Relevance
“…This signature is composed of three amino acids located at the N-terminal helix-loophelix (HLH) domain in mammals and sauropsids ( Figure 4a). According to recently published structures (Hughes et al, 2018a;Singh et al, 2017), the HLH domain sits close to the S2-S3 intracellular linker and conveniently adjacent to the TRP domain helix (TD-helix), a known modulator of TRP channel gating (Gregorio-teruel et al, 2015;Valente et al, 2008) (Figure 4b).…”
Section: Fast Inactivation Is a Functional Property Associated To Thementioning
confidence: 99%
“…This signature is composed of three amino acids located at the N-terminal helix-loophelix (HLH) domain in mammals and sauropsids ( Figure 4a). According to recently published structures (Hughes et al, 2018a;Singh et al, 2017), the HLH domain sits close to the S2-S3 intracellular linker and conveniently adjacent to the TRP domain helix (TD-helix), a known modulator of TRP channel gating (Gregorio-teruel et al, 2015;Valente et al, 2008) (Figure 4b).…”
Section: Fast Inactivation Is a Functional Property Associated To Thementioning
confidence: 99%
“…The TRPV channel subfamily members (TRPV1-TRPV6) have strong structural homology 13 , yet the effects of lipids on these channels are widely divergent [14][15][16][17][18] . Structural studies of members of this family have shown that both modulating and structural lipids can bind the "vanilloid" pocket located in the transmembrane domain (TMD) between the S3 and S4 helices and the helical S4-S5 linker of each monomer [15][16][17] . This pocket has also been shown to be a drug binding site in some TRPV channels and different occupants of this pocket can transmit conformational changes into the pore which affect gating 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies of members of this family have shown that both modulating and structural lipids can bind the "vanilloid" pocket located in the transmembrane domain (TMD) between the S3 and S4 helices and the helical S4-S5 linker of each monomer [15][16][17] . This pocket has also been shown to be a drug binding site in some TRPV channels and different occupants of this pocket can transmit conformational changes into the pore which affect gating 15,16 . This "vanilloid" pocket does not have very strong lipid density in currently available structures of TRPV2 [18][19][20] , TRPV3 21,22 and TRPV4 23 channels, while annular or modulating lipids have strong density in this pocket in TRPV1 15 , TRPV5 16 and TRPV6 17 channels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations